2020
DOI: 10.3390/polym12061271
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Polyvinylalcohol -Cellulose Derivative-Based Film with Povidone-Iodine Predicted for Wound Treatment

Abstract: The aim of this study was to develop and assess a polyvinyl alcohol-cellulose derivatives-based film with incorporated povidone-iodine (PVP-I) predicted for applications in the treatment of periodontitis. Films were fabricated by solvent-casting, and their physical characteristics, such as their surface and structure morphology, mechanical properties, and disintegrating time, were evaluated. For in vitro iodine release studies and evaluation, the antimicrobial activity was tested using a modified disc diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…The elemental analysis of EDX ( Figure S1, supplementary file ) recorded the signal of I beside that of O and C for hydrogel. In FTIR spectral analysis, absorption peak of C=O in PI (at 1627 cm −1 ) and was overlapped with that of Pe@CMP hydrogel [ 51 , 52 ]. Both of micrographs and FTIR spectra confirmed the loading of PI onto the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…The elemental analysis of EDX ( Figure S1, supplementary file ) recorded the signal of I beside that of O and C for hydrogel. In FTIR spectral analysis, absorption peak of C=O in PI (at 1627 cm −1 ) and was overlapped with that of Pe@CMP hydrogel [ 51 , 52 ]. Both of micrographs and FTIR spectra confirmed the loading of PI onto the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…The dried film is then cut into pieces of the desired size and adequately packaged. Finally, the resulting film carrier should not be exposed to ambient conditions for a prolonged period due to its susceptibility to drying, evaporation of the residual solvent and reduced flexibility, as well as to mechanical damage in the form of chipping or micro-cracking [31][32][33]. The quality of the final product prepared by solvent casting is influenced by the properties of the polymers used to prepare the casting compounds, such as molecule structure, transverse dimension, chain length and flexibility.…”
Section: Solvent-casting Methods (Scm)mentioning
confidence: 99%
“…It has been reported that, for example, PVP mixed with cellulose derivatives such as ethyl cellulose and HPC can produce films with increased flexibility and softer, more durable properties [37]. Kida et al [31] report fabricating matrices based on polyvinyl alcohol (PVA) with cellulose derivatives, i.e., hydroxypropyl methylcellulose (HPMC) or sodium carboxymethyl cellulose (CMC). PVA has excellent membrane-forming properties and has been blended with selected swelling and gelling cellulose derivatives to tailor the mechanical and physicochemical properties of the developed polymer membranes to the application requirements.…”
Section: Solvent-casting Methods (Scm)mentioning
confidence: 99%
“…The same polysaccharide, in combination with PVA, was used to obtain films by solvent casting and their physical–mechanical characteristics, morphology, mechanical properties, and disintegrating time, were evaluated. The successful incorporation of povidone-iodine and the ability of the system to deliver the drug consistently recommend it for applications in the treatment of periodontitis [ 69 ].…”
Section: Polymer–drug Systemsmentioning
confidence: 99%